Self-Employment amongst Migrant Groups in England and Wales: New Evidence from Census Microdata - Ken Clark; Stephen Drinkwater; Catherine Robinson (Institute for the Study of Labor (IZA), 2015)
Self-employment constitutes a vital part of the economy since entrepreneurs can provide not only employment for themselves but also for others. The link between self-employment and immigration is, however, complex since self-employment can be viewed as both a haven from the paid labour market or as a source of economic growth. Moreover, the nature of self-employment has changed considerably in recent decades, especially with regards to providing a flexible form of employment for many demographic groups. We investigate the evolving relationship between self-employment and immigration in the UK using recently released microdata from the 2011 Census for England and Wales. Our findings indicate large variations, with high self-employment rates observed for some groups with a long established history of migration to the UK (especially men born in Pakistan) and also for some groups who have arrived more recently (such as from the EU's new member states). We further explore the differences, analyse variations by gender and identify key determining factors. In addition to certain socio-economic characteristics, it is found that migration-related influences, such as English language proficiency and period of arrival in the UK, play an important role for some groups.
Keywords: J61; F22; J21; 330; self-employment; immigrants; United Kingdom